Differential white cell counts by frequency distribution analysis of cell volumes - Hughes-Jones, N. C. (1974)
Absolute neutrophil and lymphocyte counts on peripheral blood can be made by analysis of the output from a Coulter particle counter, utilizing the difference in the relative cell volume between these two types of cell. A comparison has been made between the results obtained by volume analysis and those obtained by standard microscopical techniques in 10 normal people and 45 patients. The absolute neutrophil count obtained by volume analysis agreed well with values obtained by microscopy; the lymphocyte count did not give such good agreement, since the smaller number of cells counted gave rise to larger sampling errors. The method of volume analysis is suitable for the assessment of absolute neutrophil counts for clinical use.